EFFECTS OF VITAMIN D ON THE RENIN-ANGIOTENSIN SYSTEM - L. Pashova-Stoyanova; A. Tolekova (Trakia Journal of Sciences)
The renin-angiotensin-aldosterone system (RAAS) is a complex endocrine system of enzymes, proteins and peptides that occupies a key position in the regulation of a number of important physiological processes, such as arterial pressure, water and electrolyte homeostasis. Its activity, flow and regulation are affected by a large number of mediators, substances and diseases one of which is vitamin D. Vitamin D is involved in the regulation of many physiological processes with great importance. Vitamin D deficiency is associated with an increased risk of impaired renal function, cardiovascular disease, diabetes mellitus, metabolic disorders, affecting RAAS and other pathways.